Nursing Implementation of Acute Pain Management in Post Mastectomy Surgery Patients - Ismar Agustin; Azwaldi; Muliyadi; Sri Endriyani; Vina Annisa Dilianasari (Universitas STRADA Indonesia, 2022)
Background: Surgery is a potential or actual threat to a person's integrity, both biopsychosocial and spiritual. One of the treatments for breast cancer is surgery, either tumor removal or mastectomy. The problem that often arises in postoperative patients is pain, which can affect the patient's overall condition. Purpose: The purpose of this study was to determine the effect of pain management with deep breath relaxation therapy on the post operative mammae pain scale. Methods: This case study design uses a descriptive method. The sampling method used was purposive sampling with 2 respondents, namely post-mastectomy patients in the Surgical Room of Muhammadiyah Hospital Palembang, in March 2022. The case study data were taken using interviews, observations and physical examinations carried out descriptively and presented in a narrative manner Results: After implementing acute post-mastectomy pain management with deep breathing relaxation therapy in both case study subjects for 3 days there was a 3 point reduction in pain scale, in patient 1 from pain scale 6 to pain scale 3, in patient 2 from pain scale 5 to a pain scale of 2, and both case study subjects were able to move and fulfill basic needs independently. Conclusion: Acute pain management with deep breathing relaxation therapy can reduce pain scale and help patients move quickly.